An Experimental Analysis of Strikes in Bargaining Games with One-Sided Private Information - Forsythe, Robert; Kennan, John; Sopher, Barry (American Economic Review, 1991)
The authors study two-player, pie-splitting games in which one player knows the pie and the other knows only its probability distribution. The authors compare treatments in which incentive-efficient strikes (disagreements) are possible with alternatives in which efficiency forbids strikes. They find that incentive-efficiency is very helpful in explaining when strikes occur. There is also evidence of substantial heterogeneity in the subjects' altruism and in their risk preferences. This means that the common-knowledge assumptions of game theory cannot be controlled in experiments; but in the authors' experiments the main theoretical conclusions seem robust to violations of these assumptions. Copyright 1991 by American Economic Association.